Um estudo da metodologia de Robert Gagné aplicada ao ensino de biofísica - Cauduro, Paola Jardim (2014)
Increasingly discusses the importance of professionals from all areas perform their work more effectively with an ability to solve interdisciplinary problems. The Biophysics is one such area involving related and contextualized knowledge of Biology, Physics, Anatomy, Physiology, Kinesiology, and that give healthcare professionals a more complete and dynamic understanding of the processes of the human body systems and operating devices increasingly complex. In order to provide the best conditions, we have investigated which are the contributions of Robert Gagné methodology for teaching Biophysics, through planning and implementation of sequences of diverse teaching four classes in the course of Physical Therapy, Universidade Federal de Santa Maria (UFSM). Each sequence had a set of external events planned according to the profile of the physiotherapist proposed by the Federal Council of Physical Therapy and Occupational Therapy (COFFITO). The sequences focused, respectively, the traditional teaching, the insertion of content revisions from high school and practical activities, problem solving and inserting Culture Circles of Freire in the first three external events. The quantitative evaluation results showed that the group who received the teaching sequence with the insertion of Culture Circles as motivator showed better performances for the content of Electromagnetic Radiation, Ultrasonography and Biophysics of Circulation and Respiration, provided by the menu of discipline. Other facts were noted that external events such as gaining attention, cause, assess performance and improve retention and transfer could not be developed successfully because of the need for more reliable instruments motivational analysis and workload favoring their implementation. These classes also questionnaires interests and behaviors were applied, in order to better understand how they think and what their attitudes to the General Physics and Biophysics discipline. However, the project developed guiding elements has had discussions that may contribute to teachers of Biophysics able to develop jobs more effectively utilizing instructional methodology with Gagné Culture Circles, allowing students to develop cognitively through a sequence well structured and based on the main difficulties of them investigated in discussion forums external events .